Evaluasi Produktivitas Sumur Horizontal Di Lapangan Jatibarang PT Pertamina EP Region Jawa - Adrian Indarti (Program Studi Akuntansi IKOPIN, 2022)
Well X-HZ1, X-HZ2, and X-HZ3 are horizontal wells of short radius type that all of them produce hydrocarbons from the volcanic layer of Jatibarang which its reservoir rock characteristic is matrix-fracture. Calculation of the horizontal PI (Jh) and vertical PI (Jv) for the existing condition in each well, note that in general Jh is much larger than Jv. For well X-HZ1, Jh = 9.42 b/d /psi, and Jv = 2.67 b/d /psi, for well X-HZ2 , Jh = 2.62 b/d/psi, and Jv = 0.44 b/d / psi, then at well X-HZ3, Jh = 7.1 b/d/psi, and Jv = 1.44 b/d /psi. Thus productivity ratio obtained for the well X-HZ1, X-HZ2, and X-HZ3 consecutively,3.53,5.98,and4.93. From the calculations of total gains till QEL known that well X-HZ1 can produce up to 421 MBbl oil, the well X-HZ2 achieve 165 MBbl and well X-HZ3 produce up to 268MBbl.